Exercise During Pregnancy and Prenatal Depression: A Systematic Review and Meta-Analysis - Sánchez-Polán, Miguel; Franco, Evelia; Silva-José, Cristina; Gil-Ares, Javier; Pérez-Tejero, Javier; Barakat, Rubén; Refoyo, Ignacio (Frontiers in Physiology, 2021)
Background: Prenatal depression is associated with an increased risk of physical, physiological, cardiovascular and psychological diseases for mothers and future newborns. Prenatal depression and depressive symptoms could have negative effects on the cognitive, emotional, social and behavioural development of children. Objective: This study aimed to examine the influence of exercise during pregnancy on the prevalence of prenatal depression and depressive symptoms in the scientific literature. Data Sources: A search was carried out examining different online databases up to November 2020. Methods of Study Selection: A systematic review with random effects meta-analysis was performed. Only randomized controlled trials (RCTs) published in English or Spanish with pregnant populations and interventions with exercise programs carried out during pregnancy were included. The scores obtained by the tools that measured the emotional state and depressive symptoms as well as the number and percentage of depressed women of the study groups were analysed. Tabulation, Integration, and Results: We analysed 15 studies and found a negative association between moderate exercise during pregnancy and prenatal depression (ES = -0.36, 95% CI = -.58, -13, I2 = 80.2%, Pheterogeneity = .001). In addition, the studies also showed that women who were inactive during pregnancy had a 16% higher probability of suffering prenatal depression (RR = 0.84 [95% IC= 0.74, 0.96] I2= 61.9%, Pheterogeneity = .010). Conclusion: Supervised exercise during pregnancy may be useful for the prevention and reduction of prenatal depression and depressive symptoms. Registration: Registered in PROSPERO (Registration No CRD42020164819).